1991
DOI: 10.1016/0035-9203(91)90226-o
|View full text |Cite
|
Sign up to set email alerts
|

Human urine stimulates growth of Leishmania in vitro

Abstract: Enhancement of trypanosomatid metacyclogenesis by insect urine components led us to test the effect of human urine as a culture additive. The addition of 1-5% urine to Schneider's Drosophila medium containing 10% foetal calf serum enhanced the growth of 11 Leishmania strains representing 8 different taxonomic groups. Cell division was stimulated in cultures with non-dividing organisms. Peak cell density was increased, as was the efficiency with which L. donovani could be isolated from infected hamsters. Prelim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
45
0
16

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 12 publications
1
45
0
16
Order By: Relevance
“…Other strains or species have been adapted to continuous growth in less rich media containing serum or with serum replaced by bovine serum albumin, 20,21 bacteriologic media, or more recently, human urine. 32,33 The complexity of the media used to cultivate members of the genus Leishmania has complicated the feasibility of comparative studies on nutritional requirements, metabolism, and other characteristics of these organisms, especially those isolated from mammals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other strains or species have been adapted to continuous growth in less rich media containing serum or with serum replaced by bovine serum albumin, 20,21 bacteriologic media, or more recently, human urine. 32,33 The complexity of the media used to cultivate members of the genus Leishmania has complicated the feasibility of comparative studies on nutritional requirements, metabolism, and other characteristics of these organisms, especially those isolated from mammals.…”
Section: Discussionmentioning
confidence: 99%
“…These media were enriched with large concentrations of certain amino acids, vitamins, bovine albumin, hormones, peptide supplements, [25][26][27][28][29][30][31] or more recently, with human urine. 32,33 In the present paper, we report a completely chemically defined culture medium free of serum, macromolecules, proteins, and peptides that readily supports the growth and maintenance of promastigote forms of various Leishmania species without compromising parasite growth rates. Morphologic, biochemical, immunologic, and biologic properties of aserically grown promastigote forms are presented.…”
mentioning
confidence: 96%
“…6 Several studies have shown the stimulatory effect of human urine on Leishmania promastigotes. [7][8][9][10][11] When supplemented with human urine, Schneider's Drosophila culture media was found to increase the proliferation of different Leishmania parasite species. In the same study, it was found that culturing amastigotes that were isolated from Leishmania -infected hamsters in a culture environment containing urine increased promastigote differentiation and proliferation compared with controls.…”
Section: Introductionmentioning
confidence: 99%
“…In the same study, it was found that culturing amastigotes that were isolated from Leishmania -infected hamsters in a culture environment containing urine increased promastigote differentiation and proliferation compared with controls. 7 Another study questioned whether urine from a healthy human donor, a patient with nephritis, and several types of animals could be an alternative to fetal calf serum (FCS) for in vitro L. donovani culture. Results have indicated that urine was not a valid alternative to FCS, but can be used to increase the proliferation in L. donovani cultures.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Howard e colaboradores demonstraram que a urina humana estimula a divisão celular in vitro de Leishmania, podendo facilitar o cultivo primário de células infectadas. 5 Armstrong e colaboradores relataram que a urina humana estéril adicionada ao meio de cultura também estimula a divisão celular de formas promastigotas e facilita o cultivo primário de células infectadas de tecido animal, podendo substituir o soro fetal bovino nos meios de cultura. 6 Foram usadas, em ambos casos, cepas já identificadas e mantidas em criopreservação.…”
Section: Introductionunclassified